Opportunities for improving animal welfare in rodent models of epilepsy and seizures - Lidster, Katie; Jefferys, John G.; Blümcke, Ingmar; Crunelli, Vincenzo; Flecknell, Paul; Frenguelli, Bruno G.; Gray, William P.; Kaminski, Rafal; Pitkanen, Asia; Ragan, Ian; Shah, Mala; Simonato, Michele; et al. (Journal of Neuroscience Methods, 2016)
Animal models of epilepsy and seizures, mostly involving mice and rats, are used to understand the pathophysiology of the different forms of epilepsy and their comorbidities, to identify biomarkers, and to discover new antiepileptic drugs and treatments for comorbidities. Such models represent an important area for application of the 3Rs (replacement, reduction and refinement of animal use). This report provides background information and recommendations aimed at minimising pain, suffering and distress in rodent models of epilepsy and seizures in order to improve animal welfare and optimise the quality of studies in this area. The report includes practical guidance on principles of choosing a model, induction procedures, in vivo recordings, perioperative care, welfare assessment, humane endpoints, social housing, environmental enrichment, reporting of studies and data sharing. In addition, some model-specific welfare considerations are discussed, and data gaps and areas for further research are identified. The guidance is based upon a systematic review of the scientific literature, survey of the international epilepsy research community, consultation with veterinarians and animal care and welfare officers, and the expert opinion and practical experience of the members of a Working Group convened by the United Kingdom's National Centre for the Replacement, Refinement and Reduction of Animals in Research (NC3Rs).
EVALuna2:7310